Brazil in Africa - Abbaspour Tazehkand, Hesameddin (Université d'Ottawa | University of Ottawa, 2014)
The aim of this paper is to examine the modern Brazil-Africa relations with an emphasis on the eight years of Lula da Silva’s presidency. History and various aspects of this relationship (such as trade, development aid and defense policy) are explored and used to extrapolate the future trajectory of Brazil-Africa relations.